2019
DOI: 10.1016/j.jes.2019.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Emission reduction characteristics of a catalyzed continuously regenerating trap after-treatment system and its durability performance

Abstract: This is a repository copy of Emission reduction characteristics of a catalyzed continuously regenerating trap after-treatment system and its durability performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…On the basis of the original DPF, the system is covered with a layer of catalyst, which is more favorable for the oxidation of soot. The CCRT system can reduce the CO and HC emissions by more than 60%, while the particle removal rate is more than 90% (Zhang et al 2019e ). The experiment was carried out by an off-road diesel engine, and it found that CCRT reduced more than 81% CO and 73% HC than a single CDPF device (Zhang et al 2019c ).…”
Section: Diesel Particulate Filter Regenerationmentioning
confidence: 99%
“…On the basis of the original DPF, the system is covered with a layer of catalyst, which is more favorable for the oxidation of soot. The CCRT system can reduce the CO and HC emissions by more than 60%, while the particle removal rate is more than 90% (Zhang et al 2019e ). The experiment was carried out by an off-road diesel engine, and it found that CCRT reduced more than 81% CO and 73% HC than a single CDPF device (Zhang et al 2019c ).…”
Section: Diesel Particulate Filter Regenerationmentioning
confidence: 99%
“…The catalyzed diesel particulate filter (CDPF) manufactured by coating noble metal catalyst such as Pt and Pd et al on the wall of DPF is being widely employed as an efficient diesel emission control technology 7 . It can not only oxidize CO, HC and increase the NO 2 proportion by oxidizing NO 8 , but also filter the particles with a high efficiency 9 , and achieve a regeneration of the CDPF by oxidizing the trapped particles with a relatively low temperature 10 . The Pt and Pd have strong catalytic activity in oxidizing CO, HC and NO.…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome this problem, the active–passive component regeneration of the DOC-assisting DPF is a traditional option . A certain amount of the fuel is injected into the cylinder in the late stage of the combustion process, or a certain amount of the fuel is injected into the exhaust pipe at the upstream of a DOC. The DOC is used to oxidize the fuel, heat the downstream DPF, and promote the passive regeneration of the DPF. In-cylinder injection of the fuel has an advantage that no additional fuel injection device is needed, whereas a main disadvantage is that the lubricating oil of the diesel engine will be diluted by the fuel.…”
Section: Introductionmentioning
confidence: 99%